Etna Bulk rock (major and trace elements) analyses 2022 (BRET_2022) - Miraglia, Lucia (Istituto Nazionale di Geofisica e Vulcanologia (INGV), 2022)
The database consist of Bulk rock compositions (major and trace elements) of lava and pyroclasts sampled at Etna during the 2022 INGV-OE petrologic monitoring activity.
Keywords: Etna; XRF; Bulk rock analyses; Major elements; Trace elements; Petrological monitoring